Simultaneous impairment of neuronal and metabolic function of mutated gephyrin in a patient with epileptic encephalopathy - Borislav Dejanovic; Tania Djémié; Nora Grünewald; Arvid Suls; Vanessa Kress; Florian Hetsch; Dana Craiu; Matthew Zemel; Padhraig Gormley; Dennis Lal; EuroEPINOMICS Dravet working group; Candace T Myers; et al. (EMBO Molecular Medicine)
Abstract Synaptic inhibition is essential for shaping the dynamics of neuronal networks, and aberrant inhibition plays an important role in neurological disorders. Gephyrin is a central player at inhibitory postsynapses, directly binds and organizes GABAA and glycine receptors (GABAARs and GlyRs), and is thereby indispensable for normal inhibitory neurotransmission. Additionally, gephyrin catalyzes the synthesis of the molybdenum cofactor (MoCo) in peripheral tissue. We identified a de novo missense mutation (G375D) in the gephyrin gene (GPHN) in a patient with epileptic encephalopathy resembling Dravet syndrome. Although stably expressed and correctly folded, gephyrin‐G375D was non‐synaptically localized in neurons and acted dominant‐negatively on the clustering of wild‐type gephyrin leading to a marked decrease in GABAAR surface expression and GABAergic signaling. We identified a decreased binding affinity between gephyrin‐G375D and the receptors, suggesting that Gly375 is essential for gephyrin–receptor complex formation. Surprisingly, gephyrin‐G375D was also unable to synthesize MoCo and activate MoCo‐dependent enzymes. Thus, we describe a missense mutation that affects both functions of gephyrin and suggest that the identified defect at GABAergic synapses is the mechanism underlying the patient's severe phenotype.